Case Report: Treatment with magnetic nanoparticle-based hyperthermia stabilizes metastatic disease in stage IV primary liver cancer patients - Kraus, Sarah; Arbib, Shir; Ventura-Bixenshpaner, Hila; Rukenstein, Pazit; Hirsh-Kovacs, Meirav; Shalev, Boaz; Eltanani, Moshe; Ron, Udi; Gumina, Olga; Shalev, Ofer; Geschwind, Jeff (Frontiers in Oncology, 2026)
The First-in-Human clinical trial of a novel magnetic nanoparticle-based hyperthermia therapy consisting of iron oxide multicore encapsulated nanoparticles, termed Sarah Nanoparticles (SaNP), administered intravenously before being exposed to alternating magnetic field (AMF) irradiation began enrolment. We report the preliminary results on two patients with advanced primary liver cancer; a 75-year-old man with advanced stage hepatocellular carcinoma and a 69-year-old woman with metastatic cholangiocarcinoma treated with a SaNP dose of 1.8 mg/kg followed by pulsed AMF irradiation for a total duration of 15 min. Toxicity assessment was performed using standard criteria for the grading of adverse events during treatment and after a follow-up period of 30 days. Tumor response was evaluated by the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1. Both patients tolerated the procedure well without any significant clinical or laboratory toxicities. Magnetic resonance imaging (MRI) analysis revealed accumulation of the SaNP in the tumors followed by clearance from the liver and spleen on T2*-weighted MR imaging. Tumor response as assessed by RECIST 1.1 demonstrated stable disease at the follow-up timepoint. Preliminary analysis of this First-in-Human trial of magnetic nanoparticle-based hyperthermia treatment for patients with advanced cancer demonstrated encouraging results both in terms of efficacy by halting disease progression and toxicity, where no significant side effects occurred.